Extending the UTAUT to Examine Factors Influencing Intention to Infaq and Sadaqah Using Mobile Banking: Evidence from Millennials Muslim in Indonesia - Uus Ahmad Husaeni (Journal of Islamic Monetary Economics and Finance, 2026)
This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) model to examine the factors that influence intentions to infaq and sadaqah using mobile banking among the millennial Muslim generation in Indonesia. In addition to UTAUT variables, namely performance expectancy, effort expectancy, social influence, and facilitating conditions, we include trust in institutions, religiosity, and habit as potential factors. Primary data gathered by means of questionnaires from 207 respondents are analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The main results indicate that performance expectancy, effort expectancy, social influence, facilitating conditions, trust in institutions, and religiosity influence the intention to infaq and sadaqah using mobile banking. However, habit does not determine the intention to infaq and sadaqah using mobile banking. The social influence is the most dominant factor. This shows that Muslim millennials in Indonesia have a fairly high social sensitivity as a form of social responsibility. It also confirms that encouragement from family, friends, and influential people around them is an important consideration for Muslim millennials to give infaq and sadaqah through mobile banking.